Assessing Armenia's potential for an AI-driven defense industry: An index-based analysis - Danielyan, Gyulnara (International Journal of Innovative Research and Scientific Studies, 2025)
The development of the AI-based defense industry is particularly important for small countries engaged in regional conflicts. In this sense, it is crucial for Armenia to consider the possibility of having an AI-based defense. Since the information on defense is data-sensitive and the available data are not sufficient to assess the country's potential, we have considered several key international economic indices that are closely related to the development of the field. The analysis focuses on indices such as the Global Innovation Index (GII), Global Competitiveness Index (GCI), ICT Development Index (IDI), Human Development Index (HDI), Global Cybersecurity Index (GCI), and AI Readiness Index, among others. The research findings have shown that Armenia has the potential to develop an innovative defense industry. Several strategic recommendations have been suggested, targeting the areas where improvements are required.